Factors Influencing the Sustainability of Integrated Coastal Management Projects in the Philippines - Pollnac, Richard B.; Thiele, Monika T.; Villahermosa Eisma, Rose-Liza; Gaudan, Wednesday Gay; Tabara, Esperanza; Dinoy, Nicel Jane; Avellana Jr., Rodolfo (Silliman Journal, 2022)
The paper examines the sustainability of integrated coastal management (ICM) activities associated with several ICM projects in the Philippines. Sustainability implies continuance of activity beyond project termination date; hence, the focus of this study is on those that ended more than 5 years ago. In the large projects examined in the research, activities were carried out in numerous municipalities and villages (barangays), and there were varying levels of sustained activities in the different project sites. This paper examines data from 42 villages in the Visayas, Batangas, and Lingayan Gulf areas of the Philippines and quantitatively elucidates socioeconomic and project activity factors related to these differences in ICM sustainability. The results indicate that social science theory and findings already in the literature can be used to account for some of the differential levels of success. As the research clearly indicates, practices related to sustainability are not always applied in actual project implementation. And even where they are, we still find mixed results suggesting that we must refine our research methods even further to determine other factors influencing ICM project sustainability.